1999
DOI: 10.1002/(sici)1096-8628(19990507)84:1<61::aid-ajmg12>3.3.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

The Meier‐Gorlin syndrome, or ear–patella–short stature syndrome, in sibs

Abstract: The Meier-Gorlin syndrome, first described by Meier and Rothschild [1959: Helv Paediatr Acta 14:213-216] and further delineated by Gorlin et al. [1975: A Selected Miscellany, p 39-50], is characterized by short stature, slender body build, craniofacial anomalies, microtia, delayed skeletal development, hypogonadism, and absence of the patellae. It has also been called the ear-patella-short stature syndrome [Boles et al., 1994: Clin Dysmorphol 3:207-214]. We report on two brothers with Meier-Gorlin syndrome, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Meier–Gorlin syndrome (MGS; OMIM 224690) is an autosomal recessive disorder with microtia, absent patellae, craniofacial anomalies, and delayed skeletal development 131. It has been suggested that this syndrome is the human equivalent of the short ear mouse model, which carries a mutation in the bone morphogenetic protein 5 ( Bmp5 ) gene 132.…”
Section: Microtia-associated Syndromes With Other Molecular Mechanismsmentioning
confidence: 99%
“…Meier–Gorlin syndrome (MGS; OMIM 224690) is an autosomal recessive disorder with microtia, absent patellae, craniofacial anomalies, and delayed skeletal development 131. It has been suggested that this syndrome is the human equivalent of the short ear mouse model, which carries a mutation in the bone morphogenetic protein 5 ( Bmp5 ) gene 132.…”
Section: Microtia-associated Syndromes With Other Molecular Mechanismsmentioning
confidence: 99%